(untitled) (Proceedings of Southern Federal University. Philology, 2020)
Modern political discourse has obtained a new level, i.e. bilateral due to the Internet. This feature of this social network lets a user make a comment to any post written on the page and, what is more, there is a high possibility that a person addressed will read it and answer it. As a comment is considered to be an individual’s speech act it can be rendered from stylistics’ point of view. Implying stylistics into speech can be explained by an attempt to cause a certain emotional reaction of a person. The given article deals with the stylistic analysis of such comments to Theresa May’s posts in “Twitter” and subsequent determination of the emotive state of the readers. Keywords: discourse, political Internet-discourse, comment, social network, stylistic means, Twitter, Theresa May. DOI 10.18522/1995-0640-2020-1-77-84